The impact of socioeconomic factors on the healthcare costs of people living with HIV in Turkey - Özdemir, Hülya Özkan (BMC Public Health, 2020)
BACKGROUND: This study addresses an important field within HIV research, the impact of socioeconomic factors on the healthcare costs of people living with HIV/AIDS (PLHIV). We aimed to understand how different socioeconomic factors could create diverse healthcare costs for PLHIV in Turkey. METHODS: Data were collected between January 2017 and December 2017. HIV-positive people attending the clinic who had been referred to the national ART programme from January 1992 until December 2017 were surveyed. The questionnaire collected socioeconomic data. The cost data for the same patients was taken from the electronic database Probel Hospital Information Management System (PHIMS) for the same period. The PHIMS data include costs for medication (highly active antiretroviral therapy or HAART), laboratory, pathology, radiology, polyclinic, examination and consultation, hospitalisation, surgery and intervention, blood and blood products, supplies and other costs. Data were analysed using STATA 14.2 to estimate the generalised linear model (GLM). RESULTS: The findings of our GLM indicate that age, gender, marital and parental status, time since diagnosis, employment, wealth status, illicit drug use and CD4 cell count are the factors significantly related to the healthcare cost of patients. We found that compared with people who have AIDS (CD4 cells < 200 cells/mm(3)), people who have a normal range of CD4 cells (≥ 500 cells/mm(3)) have $1046 less in expenditures on average. Compared to younger people (19–39 years), older people (≥ 55) have $1934 higher expenditures on average. Costs are $644 higher on average for married people and $401 higher on average for people who have children. Healthcare costs are $518 and $651 higher on average for patients who are addicted to drugs and who use psychiatric drug(s), respectively. Compared to people who were recently diagnosed with HIV, people who were diagnosed ≥10 years ago have $743 lower expenditures on average. CONCLUSION: Our results suggest that in addition to immunological status, socioeconomic factors play a substantial role in the healthcare costs of PLHIV. The key factors influencing the healthcare costs of PLHIV are also critical for public policy makers, healthcare workers, health ministries and employment community programs.